Training primary teachers through experiential geography - Caroline LEININGER-FREZAL (European Journal of Geography)
Training primary school teachers is a teaching challenge in itself. Most have a low level of education in the subject of geography and are thus not keen on teaching this discipline since they feel insecure in their knowledge of it, partly related to the fact that most high school geography teachers are historians. French teacher teach geography and history. Consequently, in order to effectively train future primary school teachers, the authors have developed a course based on experiential geography (Kold, 1984). At the beginning of the course, students’ cognitive representations regarding geography were analysed, and their teaching practices were also video recorded. Following this, the entire course is organized around a field trip or simulation games. This paper demonstrates how this experiential training approach is both highly efficient in improving students’ knowledge and skills in geography, and a very good way to change their representations of geography